The Etiology of Mental Disorders Concise, Clear and Synoptical - Látalová, Klára (Karolinum, 2022)
The textbook consists of three sections. The first offers a general overview of factors important to the etiology of mental disorders, particularly the genetic, epigenetic, environmental, and microbiomatic elements. The next part examines over two dozen significant mental disorders and details specific factors in their etiology. Finally, suggestions are made for further research in and development of the field. While primarily intended for medical students studying in English, the textbook's clear and straightforward presentation should make it useful to specialists in the fields of psychiatry and neuroscience, as well.
Keywords: Psychiatrie, psychoterapie